Role of Electromechanical Dyssynchrony Assessment During Acute Circulatory Failure and Its Relation to Ventriculo-Arterial Coupling - Andrei, Stefan; Popescu, Bogdan A.; Caruso, Vincenza; Nguyen, Maxime; Bouhemad, Belaid; Guinot, Pierre-Grégoire (Frontiers in Cardiovascular Medicine, 2022)
Introduction Two parallel paradigms of cardiovascular efficiency and haemodynamic optimisation coexist in haemodynamic research. Targeting ventriculo-arterial (VA) coupling [i.e., the ratio between arterial and ventricular elastance (EV)] and electromechanical coupling are two promising approaches in acute circulatory failure. However, validation of the parameters of electromechanical coupling in critically ill patients is ongoing. Furthermore, a unifying link between VA and electromechanical coupling may exist, as EV is correlated with different times of the cardiac cycle. Materials and Methods This study was a retrospective analysis of a prospectively collected observational database from one tertiary center ICU. We analyzed the relationship between electromechanical dyssynchrony and acute circulatory failure hemodynamics before and after treatment (i.e., fluid expansion, dobutamine, or norepinephrine infusion). The relationship between electromechanical coupling and VA coupling was also investigated. Adult patients with haemodynamic instability were included. Haemodynamic parameters, including arterial pressure, cardiac index, VA coupling, stroke work index/pressure–volume area (SWI/PVA), t-IVT, and Tei's index, were collected before and after treatment. A t-IVT of >12 s/min was classified as intraventricular dyssynchrony. Results We included 54 patients; 39 (72.2%) were classified as having intraventricular dyssynchrony at baseline. These patients with baseline dyssynchrony showed a statistically significant amelioration of t-IVT (from 18 ± 4 s to 14 ± 6 s, p = 0.001), left ventricular EV [from 1.1 (0.72–1.52) to 1.33 (0.84–1.67) mmHg mL−1, p = 0.001], VA coupling [from 2 (1.67–2.59) to 1.80 (1.40–2.21), p = 0.001], and SWI/PVA [from 0.58 (0.49–0.65) to 0.64 (0.51–0.68), p = 0.007]. Patients without baseline dyssynchrony showed no statistically significant results. The improvement in VA coupling was mediated by an amelioration of EV. All patients improved their arterial pressure and cardiac index with treatment. The haemodynamic treatment group exhibited no effect on changing t-IVT. Conclusion Acute circulatory failure is associated with electromechanical dyssynchrony. Cardiac electromechanical coupling was improved by haemodynamic treatment only if altered at baseline. The improvement of cardiac electromechanical coupling was associated with the improvement of markers of cardiocirculatory efficacy and efficiency (i.e., SWI/PVA and VA coupling). This study was the first to demonstrate a possible link between cardiac electromechanical coupling and VA coupling in patients with acute circulatory failure.